2013
DOI: 10.1021/ie401055r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Microencapsulated Phase Change Materials Containing Two-Phase Core Materials

Abstract: Microencapsulated phase change materials (MicroPCMs) containing two-phase core materials, in which polypyrrole (PPy) particles were homodispersed in n-octadecane (n-Oct), were synthesized by two-step polymerization technique using poly(methyl methacrylate-co-allyl methacrylate) as shell. The surface morphologies, phase change properties, and thermal stabilities of the microcapsules were investigated using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…This indicated that the modified CNTs were generated within the microPCMs. Wang et al 33 prepared microcapsules containing polypyrrole and C18 and discovered the same phenomenon. Moreover, the samples with the addition of modified CNTs into the polymer system were a darker gray, so it was easier to incorporate the modified CNTs into the surface layer of the microPCMs.…”
Section: Ftir Spectrasupporting
confidence: 78%
See 2 more Smart Citations
“…This indicated that the modified CNTs were generated within the microPCMs. Wang et al 33 prepared microcapsules containing polypyrrole and C18 and discovered the same phenomenon. Moreover, the samples with the addition of modified CNTs into the polymer system were a darker gray, so it was easier to incorporate the modified CNTs into the surface layer of the microPCMs.…”
Section: Ftir Spectrasupporting
confidence: 78%
“…This indicated that the modified CNTs were generated within the microPCMs. Wang et al . prepared microcapsules containing polypyrrole and C18 and discovered the same phenomenon.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…They succeeded in eliminating the supercooling from the MEPCM by adding 4-14 wt% PPy in the core, while PPy had no influence on the morphology and particle distribution of the microcapsules. A new hybrid shell of polymer/SiO2 was used by Yin et al [47] to encapsulate dodecanol as a core material. They successfully eliminated the surfactant or dispersant material by using the organically modified SiO2 particles.…”
Section: Suspension Polymerizationmentioning
confidence: 99%
“…The encapsulation technique depends on the physical and chemical properties of the materials used. To date, there are several physical and chemical methods used for the production of nano or micro capsules [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, the common problem with these methods is that they all require a complex or time-consuming preparation process.…”
Section: Introductionmentioning
confidence: 99%